Visualizing the interaction of Acanthamoeba castellanii with human retinal epithelial cells by spontaneous Raman and CARS imaging - Naemat, Abida; Sinjab, Faris; McDonald, Alison; Downes, Andy; Elfick, Alistair; Elsheikha, Hany M.; Notingher, Ioan (Wiley, 2018)
Improved understanding of the mechanism of nutrient’s uptake can enable targeted manipulation of nutrient sensing pathways in medically important pathogens to a greater degree than is currently possible. In this context, we present the use of spontaneous Raman micro-spectroscopy (RMS) and coherent anti-Stokes Raman spectroscopy (CARS) to visualise the time-dependent molecular interactions between the protozoan Acanthamoeba castellanii and host human cells. Human retinal pigment epithelial (ARPE-19) cells were prelabelled with deuterated Phe (L-Phe(D8)) and the uptake of the host derived L-Phe(D8) by A. castellanii trophozoites was measured by RMS for up to 48 hours post infection (hpi). This approach revealed a time-dependent uptake pattern of this essential amino acid by A. castellanii trophozoites during the first 24 hpi with complete enrichment with L-Phe(D8) detected in trophozoites at 48 hpi. In contrast, cell free A. castellanii trophozoites showed a modest uptake of only 16-18% L-Phe(D8) from L-Phe(D8)–supplemented culture medium after 3h, 24h and 48h hpi. CARS microscopy was successfully used to monitor the reprogramming of lipids within the trophozoites as they engaged with host cells. The methodology presented here provides new advances in the ability to analyze the kinetic of amino acid acquisition by A. castellanii from host cell and extracellular environment, and to visualize lipid reprogramming within the trophozoite.